The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/met7030094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on the Microstructure and Mechanical Properties of Nitrogen-Alloyed High-Mn Austenitic Hot Work Die Steel

Abstract: Abstract:In view of the requirements for mechanical properties and service life above 650 • C, a high-Mn austenitic hot work die steel, instead of traditional martensitic hot work die steel such as H13, was developed in the present study. The effect of heat treatment on the microstructure and mechanical properties of the newly developed work die steel was studied. The results show that the microstructure of the high-Mn as-cast electroslag remelting (ESR) ingot is composed of γ-Fe, V(C,N), and Mo 2 C. V(C,N) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Dissolution of these carbides requires a particular heat treatment (holding at 1000°C to 1100°C and cooling in the water). The obtaining of the enriched austenite free of precipitates at grain boundaries affects positively hardness and wear resistance [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Dissolution of these carbides requires a particular heat treatment (holding at 1000°C to 1100°C and cooling in the water). The obtaining of the enriched austenite free of precipitates at grain boundaries affects positively hardness and wear resistance [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The substitution of Ni with Mn and nitrogen has been proven to be successful in the production of austenitic stainless steels. In addition to stabilizing austenitic structures, nitrogen is known to reduce the stacking fault energy of austenitic stainless steels, resulting in a number of beneficial effects such as enhanced strength, fatigue resistance, and impact and fracture resistances [1][2][3][4][5]. Since nickel is known to be an allergen, nickel-less and/or nickel-free stainless steels are expected to be favored, especially for biomedical applications [6].…”
Section: Introductionmentioning
confidence: 99%
“…The optimization of heat treatments such as austenitizing and tempering was also attempted to improve high-temperature stability, strength and toughness of the steel [13,24]. Heat treatments were designed to optimize the austenitic grain size, solute content and precipitation [25], increasing hardness and impact toughness [26]. It is reported that proper quenching-partitioning-tempering treatment could improve the fatigue resistance of 20Mn2SiCrNiMo bainite/martensite multiphase steels due to the presence of leaf-shaped bainite and refined retained austenite [27].…”
Section: Introductionmentioning
confidence: 99%